FEATURES OF DEVELOPMENT AND MANIFESTATION OF NEGATIVE PSYCHO-EMOTIONAL STATES IN FIRST-YEAR STUDENTS (Psychology Travelogs, 2023)
The article deals with the problem of development and manifestation of negative psycho-emotional states in first-year students of higher education institutions. The article clarifies the essence of the concepts of "personality state", "psycho-emotional state", "negative psycho-emotional state".The article reveals the existing problems of the development of negative psycho-emotional states in students during their studies at the educational institution. The authors of the article found that the external factors of the development of negative psycho-emotional states of students include socio-psychological environment, social conditions of their formation and self-affirmation, and the internal factors of the emergence of negative psycho-emotional states of students are their biological, personal and individual characteristics.The authors of the article conducted a diagnostic study of the peculiarities of the development and manifestation of negative psycho-emotional states in first-year students majoring in "Psychology" of Khmelnytsky National University. The results of the study showed that students from the first days of studying in higher education institutions experience various manifestations of negative psycho-emotional states, which are characterized by negative emotions, cognitive impairment, somatic and vegetative disorders.The authors of the article developed and substantiated methods and techniques for neutralizing negative psycho-emotional states in students as a factor of self-preservation of their health.
Keywords: personality state; negative psycho-emotional state; student youth; development and manifestations of negative psycho-emotional states of students; prevention of negative psycho-emotional states in students